Isolation of xylan degrading microorganism from local hot spring - Mohd Nizam, Zakariya (2008)
The purpose of this study was to isolate xylan-degrading microorganisms from local hot spring. The samples were taken from a local hot spring at Sungai Klah, Perak. They were screened for the best xylan degrader by using selective culture media. Then, the xylan degrader microorganism was characterized by using four staining method which were gram staining, acid-fast staining, simple staining and spore staining. The morphology of the microorganism was observed after all the staining was done by observing the changes of the staining colour. Based on the results, the microorganism was in rod shaped for simple staining, gram negative for gram staining, positive results for both spore and acid-fast staining. In conclusion, this staining method can be used to characterize the microorganism based on general information, so the microorganism was probably in genus Bacillus.